Intake of caffeine from all sources and reasons for use by college students. Issue 2 (April 2019) - Mahoney, Caroline R.; Giles, Grace E.; Marriott, Bernadette P.; Judelson, Daniel A.; Glickman, Ellen L.; Geiselman, Paula J.; Lieberman, Harris R.
Summary: Background & aims: Caffeine intake in a convenience sample of U.S. college students (N = 1248) was surveyed at five geographically-dispersed United States (U.S.) universities. Methods: Intake from coffee, tea, soft drinks, energy drinks, gums, and medications was assessed. Associations between caffeine intake and demographic variables including sex, age, race/ethnicity, family income, general health, exercise, weight variables and tobacco use were examined. Reasons for use of caffeine-containing products were assessed. Results: Caffeine, in any form, was consumed by 92% of students in the past year. Mean daily caffeine consumption for all students, including non-consumers, was 159 mg/d with a mean intake of 173 mg/d among caffeine users. Coffee was the main source of caffeine intake in male (120 mg/d) and female (111 mg/d) consumers. Male and female students consumed 53 vs. 30 mg/d of caffeine in energy drinks, respectively, and 28% consumed energy drinks with alcohol on at least one occasion. Students provided multiple reasons for caffeine use including: to feel awake (79%); enjoy the taste (68%); the social aspects of consumption (39%); improve concentration (31%); increase physical energy (27%); improve mood (18%); and alleviate stress (9%). Conclusions: As in the general U.S. population, coffee is the primary source of caffeine intake among the college students surveyed. Energy drinks provide less than half of total daily caffeine intake but more than among the general population. Students, especially women, consume somewhat more caffeine than the general population of individuals aged 19–30 y but less than individuals aged 31–50 y.